2016
DOI: 10.4172/jpb.1000396
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oxygen on Bile Resistance in Listeria monocytogenes

Abstract: Listeria monocytogenes is a Gram-positive facultative anaerobe that is the causative agent of the disease listeriosis. The infectious ability of this bacterium is dependent upon resistance to stressors encountered within the gastrointestinal tract, including bile. Previous studies have indicated bile salt hydrolase activity increases under anaerobic conditions, suggesting anaerobic conditions influence stress responses. Therefore, the goal of this study was to determine if reduced oxygen availability increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…While a previous proteomic study of L. monocytogenes (Payne et al, 2013 ) identified alterations in levels of proteins associated with DNA repair, chaperone activity, and oxidative stress response in response to bile exposure under anaerobic and neutral pH conditions, it did not detail either a pan or core bile stimulon (Payne et al, 2013 ). Similarly, a more recent proteomic study also identified a number of genes induced in L. monocytogenes in response to bile stress under neutral pH aerobic and anaerobic conditions, but did not detail an overall bile stimulon (Wright et al, 2016 ). However, a transcriptomic study of the bile regulon for L. monocytogenes 10403S, also using bile exposure at neutral pH (Quillin et al, 2011 ), confirmed a large rearrangement of the transcriptomic landscape after bile exposure with 391 differentially expressed genes after bile exposure; similar to our findings this response was characterized by up-regulation of many cellular processes including cell wall processes and transport related functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a previous proteomic study of L. monocytogenes (Payne et al, 2013 ) identified alterations in levels of proteins associated with DNA repair, chaperone activity, and oxidative stress response in response to bile exposure under anaerobic and neutral pH conditions, it did not detail either a pan or core bile stimulon (Payne et al, 2013 ). Similarly, a more recent proteomic study also identified a number of genes induced in L. monocytogenes in response to bile stress under neutral pH aerobic and anaerobic conditions, but did not detail an overall bile stimulon (Wright et al, 2016 ). However, a transcriptomic study of the bile regulon for L. monocytogenes 10403S, also using bile exposure at neutral pH (Quillin et al, 2011 ), confirmed a large rearrangement of the transcriptomic landscape after bile exposure with 391 differentially expressed genes after bile exposure; similar to our findings this response was characterized by up-regulation of many cellular processes including cell wall processes and transport related functions.…”
Section: Discussionmentioning
confidence: 99%
“…However, once bile is released into the duodenum postprandially, it becomes active in this low pH environment (Dowd et al, 2011 ). Previous proteomic and transcriptomic studies of the L. monocytogenes bile stimulon have been performed under aerobic and anaerobic conditions but at neutral pH (Quillin et al, 2011 ; Payne et al, 2013 ; Wright et al, 2016 ). To better understand the response of L. monocytogenes to conditions encountered in the proximal part of the small intestine, we characterized the transcriptomic response triggered by exposure to 1.1% bile in an acidic (pH 5.5) environment in two strains of L. monocytogenes representing lineages I and II.…”
Section: Introductionmentioning
confidence: 99%
“…Strain MNZ41 and JLB01 proteomes were evaluated using differential expression analysis based on peptide precursor mass ion current performed using the Perl programing language as described previously ( 55 ). Briefly, for each identified peptide, elution curves were integrated and organized by protein and then technical replicate.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary bile acids inhibit the germination and growth of C. difficile in the colon. Bile acids are released and mostly reabsorbed upstream in the small intestine, decreasing greatly in concentration further downstream ( 227 , 228 ). However, small intestinal microbiota can inhibit re-absorption by deconjugating bile acids, thus promoting their excretion down and out of the large intestine ( 229 ).…”
Section: Long-reaching Protectionmentioning
confidence: 99%